A PHD12–Snail2 repressive complex epigenetically mediates neural crest epithelial-to-mesenchymal transition - Strobl Mazulla, Pablo Hernan (2012)
Neural crest cells form within the neural tube and then undergo an epithelial to mesenchymal transition (EMT) to initiate migration to distant locations. The transcriptional repressor Snail2 has been implicated in neural crest EMT via an as of yet unknown mechanism. We report that the adaptor protein PHD12 is highly expressed before neural crest EMT. At cranial levels, loss of PHD12 phenocopies Snail2 knockdown, preventing transcriptional shutdown of the adhesion molecule Cad6b (Cadherin6b), thereby inhibiting neural crest emigration. Although not directly binding to each other, PHD12 and Snail2 both directly interact with Sin3A in vivo, which in turn complexes with histone deacetylase (HDAC). Chromatin immunoprecipitation revealed that PHD12 is recruited to the Cad6b promoter during neural crest EMT. Consistent with this, lysines on histone 3 at the Cad6b promoter are hyperacetylated before neural crest emigration, correlating with active transcription, but deacetylated during EMT, reflecting the repressive state. Knockdown of either PHD12 or Snail2 prevents Cad6b promoter deacetylation. Collectively, the results show that PHD12 interacts directly with Sin3A/HDAC, which in turn interacts with Snail2, forming a complex at the Cad6b promoter and thus revealing the nature of the in vivo Snail repressive complex that regulates neural crest EMT.